CONTEMPORARY MENTAWAI RECAPITULATES ANCESTRY: THE POSITION OF WOMEN IN SIBERUT SOCIETY - Maskota Delfi (Humaniora, 2013)
The indigenous Mentawaians, who reside on Siberut Island, the archipelago off the west coast of Sumatera, are located in communities whose culture and cosmology stem from the traditions of Arat Sabulungan. The guidance is valuable for the social relation of the community, nevertheless the practise subordinates certain groups in society, especially women. For example, the gender roles in particular for women stem from the traditional norms of Arat. However it is essentially a social construct that favours men, and has been perpetuated through cultural practices. The continuing position of women is being subordinated to male dominance, which has led to resistance from women. Male dominance built on truth claims derived from indigenous legitimacy in arat, is resisted by women. Women are now constructing their own truth claims, and are questioning the status quo.